The effect of settler farming on indigenous agriculture: Evidence from Italian Libya - Bertazzini, M (Wiley, 2022)
What effect did the settlement of European farmers have on the indigenous agricultural sector during the colonial period? On the one hand, European immigrants imported skills and capital but, on the other, they took control of local resources. By looking at the short-term effect of Italian farming in colonial Libya, I shed new light on this question. Through regression analysis on a novel village dataset covering the entire country, I show that, in 1939, proximity to Italian farms was associated with significantly lower land productivity relative to distant locations. Lower yields can be explained by the adoption of land-extensive cultivation techniques, implemented by indigenous farmers to counteract a labour drain operated by Italian farms through factor markets. The combined mitigating effect of monetary wages and land-extensive farming only partially compensated for the fall in income linked to reduced land productivity.